2017
DOI: 10.1248/bpb.b16-00567
|View full text |Cite
|
Sign up to set email alerts
|

Cinepazide Maleate Improves Cognitive Function and Protects Hippocampal Neurons in Diabetic Rats with Chronic Cerebral Hypoperfusion

Abstract: To determine the combined effect of type 2 diabetes (T2D) and chronic cerebral hypoperfusion (CCH) on learning and spatial memory, we developed a rat model of CCH by permanent occlusion of bilateral common carotid arteries (2-vessel occlusion (2VO)) in high-fat diet (HFD)-fed rats injected with low-dose streptozotocin (STZ). Furthermore, we examined the effect of cinepazide maleate (CM) on cognitive deficits and brain damage in this rat model. Rats were maintained on HFD for 6 weeks and then injected with 35 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The pronounced deletion of the neurons in the hippocampus is related to aggravated damages of animal behavior disorder, such as the performance in spatial learning and memory. 21) The present studies confirmed that more than 80% of the neurons in the hippocampus were damaged after a 5-min occlude in HE staining and Nissl staining. It was also noticeable that NITyr significantly reduce neuronal damage and provided adequate protection for the hippocampus, including neuronal loss, smaller size, irregular shape, deepened cytoplasm, and atrophic nuclei.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The pronounced deletion of the neurons in the hippocampus is related to aggravated damages of animal behavior disorder, such as the performance in spatial learning and memory. 21) The present studies confirmed that more than 80% of the neurons in the hippocampus were damaged after a 5-min occlude in HE staining and Nissl staining. It was also noticeable that NITyr significantly reduce neuronal damage and provided adequate protection for the hippocampus, including neuronal loss, smaller size, irregular shape, deepened cytoplasm, and atrophic nuclei.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, we selected 10 mg/kg NITyr for subsequent experiments. Nimodipine has been widely used in the treatment of brain injury, 20) there it is used as a positive drug in the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…As a major risk factor for T2DM, obesity is closely associated with insulin resistance, which can be induced by HFD [23,24]. Moreover, a low dose of STZ has been widely used to induce T2DM in rodents by targeting beta cells [17,25]. Accordingly, rats were fed a HFD to produce insulin resistance, followed by a low-dose STZ injection to induce beta cell dysfunction and subsequently hyperglycemia [26].…”
Section: Discussionmentioning
confidence: 99%
“…After 1 week of adaptive feeding, the rats were randomly divided into four groups: sham non-diabetic rats (low-fat control diet, LFD + sham) (Sham), sham T2DM rats (high-fat diet + streptozotocin, HFD + STZ + sham) (DM), hypoperfused group (LFD + BCCAO) (CCH), and hypoperfused T2DM rats (HFD+STZ+BCCAO) (DM CCH) (each group n = 9). The T2DM rat model was developed according to the method in our previous study with slight modifications [17]. LFD consisted of 10% fat, 70% carbohydrate, and 20% protein, while HFD consisted of 60% fat, 20% carbohydrate, and 20% protein.…”
Section: Model Of Diabetic Rats With Chronic Cerebral Hypoperfusionmentioning
confidence: 99%
“…However, the extent of islet β cell damage is dose-dependent ( 9 ). Following investigation of STZ dosage, 35 mg/kg has been identified as the optimal dosage of STZ to induce DM ( 10 , 11 ). Furthermore, increased doses of STZ have been associated with increased mortality in animals ( 12 ).…”
Section: Introductionmentioning
confidence: 99%